2023
DOI: 10.3390/fermentation9110973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkaline Mineral Complex Buffer Supplementation on Rumen Fermentation, Rumen Microbiota and Rumen Epithelial Transcriptome of Newborn Calves

Xiaowei Wang,
Cheng Guo,
Xiaofeng Xu
et al.

Abstract: Alkaline mineral complex buffer can improve rumen fermentation and affect the rumen microbiota of dairy cows. Here, we studied the effects of alkaline mineral complex buffer on serum immunity indexes, rumen fermentation and the microbiota of newborn calves. We also investigated changes in the rumen epithelial transcriptome expression profile. Compared with the control group, at 15 d, the serum contents of TP and GLB in the treatment group increased significantly (p < 0.05). At 30 d, the serum contents of GL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…The microflora changes of growing ewes in this study also supports the idea that feeding them hydroponic wheat sprouts might improve their immune systems. It was found that an increase in the abundance of Olsenella was considered to improve immunity in calves [ 21 ]. Moreover, Olsenella was also considered to strengthen the immunoregulation capacity of a goat model [ 22 ] and mouse model [ 23 ] host.…”
Section: Discussionmentioning
confidence: 99%
“…The microflora changes of growing ewes in this study also supports the idea that feeding them hydroponic wheat sprouts might improve their immune systems. It was found that an increase in the abundance of Olsenella was considered to improve immunity in calves [ 21 ]. Moreover, Olsenella was also considered to strengthen the immunoregulation capacity of a goat model [ 22 ] and mouse model [ 23 ] host.…”
Section: Discussionmentioning
confidence: 99%